2015
DOI: 10.1016/j.wem.2014.12.025
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study: Rare Lepiota brunneoincarnata Poisoning

Abstract: Amatoxin poisoning from the genus Lepiota may have a deadly outcome, although this is not seen as often as it is from the genus Amanita. In this report, we present a patient who was poisoned by a sublethal dose of Lepiota brunneoincarnata mushrooms. The patient was hospitalized 12 hours after eating the mushrooms. The patient's transaminase levels increased dramatically starting on day 4. Aspartate transaminase peaked at 78 hours. Starting at 1265 IU/L, alanine transaminase peaked at 90 hours at 5124 IU/L. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…As in earlier research, there was no significant rise in alkaline phosphatase levels [ 28 ]. This pattern of liver injury is similar to Amanita species poisonings, whereas few previous reports of Lepiota species only mentioned increased ALT and ALT/AST ratios [ 13 , 29 , 30 ]. Furthermore, few prior publications of Amanita poisonings have mentioned fatty changes in the liver in severe instances, and most of these fatty changes were described by radiology without pathologic confirmation [ 7 , 26 , 29 , 31 ].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…As in earlier research, there was no significant rise in alkaline phosphatase levels [ 28 ]. This pattern of liver injury is similar to Amanita species poisonings, whereas few previous reports of Lepiota species only mentioned increased ALT and ALT/AST ratios [ 13 , 29 , 30 ]. Furthermore, few prior publications of Amanita poisonings have mentioned fatty changes in the liver in severe instances, and most of these fatty changes were described by radiology without pathologic confirmation [ 7 , 26 , 29 , 31 ].…”
Section: Discussionsupporting
confidence: 75%
“…As mycological knowledge has advanced, more Lepiota species with comparable toxicity have been described more recently [ 26 ]. Even though radioimmunologic methods and thin-layer chromatography revealed a discrepancy regarding the level of amanitin in Lepiota and Amanita species, chemical analysis revealed the presence of alpha amanitin and occasionally gamma amanitin, but no beta amanitin or phallotoxins in Lepiota as opposed to Amanita [ 13 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, although several Amanita species represent the most notorious source of amatoxins and are responsible for most fatal mushroom poisonings worldwide (Enjalbert et al, 2002;Tang et al, 2016;Wei et al, 2017;Diaz, 2018;Walton, 2018), fatal intoxications after ingestion of amatoxin-containing species of Lepiota also occur (Sgambelluri et al, 2014;Diaz, 2018). Lepiota poisonings have been reported in Europe, America, Asia, and North Africa (Tunisia) (Paydas et al, 1990;Watling, 1991;Ramirez et al, 1993;Khelil et al, 2010;Kervégant et al, 2013;Kose et al, 2015;Cai et al, 2018;Diaz, 2018;Sun et al, 2019), and the most frequently reported fatal cases are due to L. brunneoincarnata and L. subincarnata (Roux et al, 2008;Khelil et al, 2010;Mottram et al, 2010;Diaz, 2018;Sun et al, 2019). Lethal Lepiota species usually produce more than one type of amatoxin, for example, L. brunneoincarnata contains both αand β-amanitin (Yilmaz et al, 2015), whereas αand γ-amanitin are present in L. josserandii (Sgambelluri et al, 2014;Walton, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, although several Amanita species represent the most notorious source of amatoxins and are responsible for most fatal mushroom poisonings worldwide ( Enjalbert et al, 2002 ; Tang et al, 2016 ; Wei et al, 2017 ; Diaz, 2018 ; Walton, 2018 ), fatal intoxications after ingestion of amatoxin-containing species of Lepiota also occur ( Sgambelluri et al, 2014 ; Diaz, 2018 ). Lepiota poisonings have been reported in Europe, America, Asia, and North Africa (Tunisia) ( Paydas et al, 1990 ; Watling, 1991 ; Ramirez et al, 1993 ; Khelil et al, 2010 ; Kervégant et al, 2013 ; Kose et al, 2015 ; Cai et al, 2018 ; Diaz, 2018 ; Sun et al, 2019 ), and the most frequently reported fatal cases are due to L . brunneoincarnata and L .…”
Section: Discussionmentioning
confidence: 99%
“…Mushrooms that contain cyclopeptide amatoxins are the most toxic species known, and more than 90% of the fatal incidents are due to this type of mushroom poisoning (Karlson-Stiber, Persson 2003;Yilmaz et al, 2015). Amatoxins are present in several Amanita mushroom species, which include several members of the Lepiota and Gallerina mushrooms (Kaya et al, 2013;Kose et al, 2015). Amatoxins can be divided into different subgroups, including alpha-amanitin, betaamanitin, gamma-amanitin, epsilon-amanitin, amanullinic acid, amanullin, proamanullin, amanin and amaninamide (Vetter, 1998); the toxin constituents vary among and within different species.…”
Section: Introductionmentioning
confidence: 99%